Age and seasonal changes of morpho-physiological state of cyprinids reared by ranching technology in conditions of the southern Ukraine - Y. Volichenko; S. Penteluk; I. Sherman (Ribogospodarsʹka Nauka Ukraïni, 2017)
Purpose. To examine the dynamics of hematological parameters of cyprinids during winter and to determine certain relationships of these or other internal parameters of the experimental groups of the young-of-the-year and yearlings.